Un'opera completata - Paganelli, Carlo (1999)
Oficinas del Banco Hypovercins Bank en Munich por Walther + Bea Betz, Eberhard Mehner
Keywords: BETZ ARCHITECTS; BETZ, WALTHER; MEHNER, EBERHARD; BANCOS; CERRAMIENTOS; BETZ, BEA